2015
DOI: 10.1038/tp.2015.166
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity-dependent and -independent mechanisms of chronic deep brain stimulation in stressed rats

Abstract: Chronic ventromedial prefrontal cortex (vmPFC) deep brain stimulation (DBS) improves depressive-like behaviour in rats via serotonergic and neurotrophic-related mechanisms. We hypothesise that, in addition to these substrates, DBS-induced increases in hippocampal neurogenesis may also be involved. Our results show that stress-induced behavioural deficits in the sucrose preference test, forced swim test, novelty-suppressed feeding test (NSFT) and elevated plus maze were countered by chronic vmPFC DBS. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…As such, axons from IL cells undergoing depolarization block, fibers en passant, and those innervating the stimulated target would still be responsive and may be activated at 130 Hz (Hamani et al, 2010). Under these circumstances, the net effect of IL DBS would correspond to that of an excitation, with IL projections being tonically driven and able to release neurotransmitters, increase BDNF levels, and enhance plasticity in downstream structures (eg, brainstem, amygdala, hippocampus) as well as in the target region (Bambico et al, 2015;Hamani et al, 2010).…”
Section: Prefrontal Cortexmentioning
confidence: 99%
“…As such, axons from IL cells undergoing depolarization block, fibers en passant, and those innervating the stimulated target would still be responsive and may be activated at 130 Hz (Hamani et al, 2010). Under these circumstances, the net effect of IL DBS would correspond to that of an excitation, with IL projections being tonically driven and able to release neurotransmitters, increase BDNF levels, and enhance plasticity in downstream structures (eg, brainstem, amygdala, hippocampus) as well as in the target region (Bambico et al, 2015;Hamani et al, 2010).…”
Section: Prefrontal Cortexmentioning
confidence: 99%
“…Beside changes in neurochemical and neurotrophin profiles, neuroplasticity changes induced by DBS have also been investigated. For instance, Bambico et al reported increased hippocampal neurogenesis and BDNF levels after vmPFC-DBS, which led to anti-anhedonic-like behaviors, but was not sufficient for an overall antidepressant-like effect [ 98 ]. Correspondingly, Liu et al found a correlation between vmPFC-HFS and hippocampal neurogenesis and improvements in short- and long-term memory in middle-aged rats.…”
Section: Preclinical Studies Of Electrical Stimulation In the Medimentioning
confidence: 99%
“…In contrast, Winter et al showed that 1 h of vmPFC-DBS with established DBS parameters in rodents did not increase the percentage of BrdU and Dcx double-stained cells in the dentate gyrus compared to the control [ 123 ]. Although research on the interaction between neurogenesis and substrates such as serotonin is ongoing, BDNF may be required to exert this antidepressant-like effect [ 98 ]. Neurogenesis is a widely investigated mechanism of DBS and these results indicate positive effects in the hippocampal region.…”
Section: Potential Mechanisms Of Stimulation-induced Antidepressanmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been primarily evaluated in the hippocampus with more limited evaluation of the SVZ and RMS. Stimulation of the anterior thalamus ( Hamani et al, 2011 ), nucleus accumbens ( Schmuckermair et al, 2013 ), ventromedial PFC ( Bambico et al, 2015 ), entorhinal cortex ( Stone et al, 2011 ), and medial septum ( Jeong et al, 2014 ) have all been demonstrated to increase neurogenesis. Importantly neurogenesis has also been demonstrated in humans.…”
Section: Regenerative Aspects Of Nbm Dbsmentioning
confidence: 99%